Optimasi Proses Pengeringan Vegetable Noodle Menggunakan Tray Dryer Infrared - Yulia, Indri; Evelyn; Zahrina, Ida (Department of Chemical Engineering, Faculty of Engineering, UNRI, 2025)
Noodles are one of the most popular processed foods due to their convenience, affordability, and ease of preparation. However, conventional noodles are primarily made from wheat flour, which lacks dietary fiber and micronutrients. Therefore, this study aims to develop a more nutritious vegetable-based noodle by incorporating local ingredients such as sago flour and pakcoy. The objective was to evaluate the effect of flour ratio (wheat:sago), drying temperature, and time on the chemical and microstructural properties of pakcoy-based dried noodles using infrared tray drying. The experimental design applied Response Surface Methodology (RSM) with Central Composite Design (CCD). Responses measured included moisture content, protein content, carbohydrate content, FTIR spectral analysis, and surface morphology via SEM. The optimal condition was achieved at a flour ratio of 85:15, drying temperature of 80°C, and 2 hours duration, resulting in 9.66% moisture, 11.79% protein, and 76.41% carbohydrates. FTIR analysis confirmed the preservation of key functional groups of carbohydrates and proteins, while SEM analysis revealed a more compact and uniform surface structure in noodles containing pakcoy. This study recommends the application of infrared drying technology in vegetable noodle processing to improve nutritional value and structural integrity